Pollutant Burden on Pollution Sources in the Wai Batu Merah Watershed, Sirimau District, Ambon City - Matulessy, Riddo Charles; Kunu, Pieter J.; Kaya, Elizabeth (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aims to identify sources of pollution and determine the magnitude of the potential pollution load from pollutant sources in the Wai Batu Merah watershed, Sirimau District, Ambon City. The method for identifying sources of pollution is carried out by using saturated or census sampling methods, calculating pollutant loads using direct methods for point source pollutant sources and indirect methods for non-point sources . The direct calculation method uses wastewater discharge data and the results of wastewater quality analysis results from measurements directly at the point source pollutant wastewater treatment plant (WWTP). The wastewater sampling technique uses the grab sampling method. While the indirect method uses effluent factors and supporting data from non-point source pollution sources that have been identified in the Wai Batu Merah watershed. The results showed that the pollutant sources found in the Wai Batu Merah watershed were point sources originating from hotel and health facility activities and non-point sources originating from domestic activities from residential areas, agricultural and livestock businesses, non-point source land (forest and open land), micro, small and medium enterprises (MSMEs), small scale industries and waste. The dominant pollutant source in the Wai Batu Merah watershed comes from domestic non-point sources. The highest point source pollution loads for BOD, COD and TSS parameters in the Wai Batu Merah watershed came from hotel activities in segment 6 with the contribution of each parameter of 17.82 kg/day, 23.82 kg/day and 0.029 kg/day. Meanwhile, the highest non-point source pollution load for BOD, COD and TSS parameters came from non-point source waste in segment 6 with the contribution of each parameter of 2825.3 kg/day, 3884.8 kg/day and 2684.03 kg/day.